Secured Storage for Dynamic Data in Cloud (Informatica, 2015)
Cloud is a growing computing paradigm in which the services and resources are provisioned dynamically through internet. In cloud, the users’ data can be stored in the remotely located data servers that are maintained by cloud service providers to relieve the users from the local storage and maintenance. The major security challenge with cloud computing is that the users cannot have direct control over the remotely stored data. The imperative security concerns in cloud   are the integrity and   confidentiality of data. Many existing remote integrity checking methods  fail to serve for the data that can be dynamically updated. To preserve the privacy of dynamically changing data, an efficient approach maintaining the confidentiality and assuring the integrity of data   is proposed. In this scheme, public auditability is enabled by introducing a Third Party Auditor (TPA) for verifying the data integrity. It is ensured that the data stored in the untrusted cloud server is confidential and consistent   by using a data encryption algorithm called 2-Keys Symmetric Encryption. Unlike other encryption algorithms, this encryption algorithm needs lesser computation overhead. Encryption and decryption algorithms are developed in java and Remote Method Invocation (RMI) concepts are used for communication between client and server. Simulation environment is set up with the eucalyptus tool. The performance analysis and simulation results prove that our proposed scheme is secure and proficient and it reduces the computation cost of server and verifier.